Morphological and chemotaxonomical characterization of some species of the genus Euphorbia L. in Jazan region, KSA - Yehia Hazzazi; Mari Sumayli; A. El-Shabasy; Abeer Al-Andal; Uzma Hanif; Asmaa Khamis; Emad Abada; Sameh R. Elgogary; Taha A. I. El-Bassossy; Ahmed A. M. Abdelgawad (PLoS ONE, 2025)
This study decisively evaluates the classification of four species of Euphorbia : Euphorbia ammak , Euphorbia fractiflexa , Euphorbia granulata , and Euphorbia hirta , collected from diverse habitats in Jazan region (Saudi Arabia). Our objective is to clearly define the interrelationships among these species by utilizing both traditional morphological analyses and cutting-edge chemotaxonomical methods. The morphological analysis examines various aspects of plant life, encompassing qualitative and quantitative parameters. Phytochemical analysis effectively measures total phenolics, alkaloids, flavonoids, saponins, and tannins. High-Performance Liquid Chromatography (HPLC) is employed to capture the phenolic patterns, thereby validating our chemotaxonomic approach. The HPLC analysis unequivocally identifies eleven phenolic and seven flavonoid compounds in the methanol extracts of the four Euphorbia taxa. The data collected from the studied Operational Taxonomic Units (OTUs) were meticulously organized into a binary matrix, establishing a similarity matrix and phenogram cluster. Duncan’s range test robustly determines the significance of interrelations among the species. The results demonstrate that all examined plant species are rich in phenolic constituents, albeit in varying concentrations. Notably, Euphorbia granulata stands out as the most transitional species among them. Taxonomically, our phenogram, based on taxonomic characteristics, reveals two distinct groups: the first group, at a distance of 1.90, includes Euphorbia ammak and Euphorbia fractiflexa , while the second group, at a distance of 1.52, encompasses the remaining two species. This study strongly recommends considering both adaptation and habitat type when conducting chemotaxonomic analyses of plant species.